Rare case of sudden onset sensorineural hearing loss in a patient diagnosed with sarcoidosis. Issue 7 (12th July 2022) - Wong, Jeremy; Leach, Laura; Chen-Xu, Michael; Truman, Lucy
Abstract : We report the case of a woman in her 30s who was referred to the ear, nose and throat department with sudden onset left-sided sensorineural hearing loss (SNHL), left anterior uveitis and erythematous lower limb lesions with bilateral pitting oedema. Based on her symptoms, an underlying inflammatory systemic disease was suspected. Autoantibodies were negative but an X-ray and high-resolution CT scan of the chest were suggestive of sarcoidosis, which was confirmed on endoscopic bronchial biopsy. Following treatment with a course of oral steroids, the patient's hearing has improved but she still suffers from episodes of uveitis. While immune-mediated inner ear disorders are a recognised cause of SNHL, sarcoidosis is a very rare cause. This case demonstrates the importance of screening for systemic autoimmune aetiology in SNHL and highlights the importance of an effective multidisciplinary team in the diagnosis and management of these patients.